A fast and practical method for determining particle size and shape by using smartphone photogrammetry. (April 2022) - An, Pengju; Tang, Huiming; Li, Changdong; Fang, Kun; Lu, Sha; Zhang, Jiefei
Highlights: A 3D image analysis method based on smartphone photogrammetry was developed for determining particle size and shape. DEMs obtained from smartphone photogrammetry were utilized to estimate the morphological characteristics of the particles. The particle size measured by the 3D image analysis method have good consistency with those of the hand measurement. The 3D image analysis method is characterised by being fast and practical and is suitable for use in field conditions. Abstract: Over the past few decades, various image-based approaches for quantifying particle morphological indicators have been developed. But most of these methods are not applicable to field conditions. This study provides a fast and practical method for determining particle size and shape based on smartphone photogrammetry. Digital elevation models (DEMs) of the particles were created by using structure from motion photogrammetry and utilized to estimate the morphological characteristics of the particles. The size and shape of 110 coarse particles were determined by the proposed method and compared with the sieving method, hand measurement, and 2D image analysis method. The results show that the method is highly practical, with the measurement accuracies for particle length, width, and thickness being −2.7% ± 6.3%, −1.8% ± 9.9%, and 10.1% ± 11.5%, respectively. The proposed method has the potential to become a popular method for measuring particle size and shape in field conditions.